FORMULASI DAN EVALUASI SEDIAAN KRIM PEWARNA RAMBUT KOMBINASI EKSTRAK BUNGA TELANG (Clitoria ternatea L.) DAN BUNGA ROSELLA (Hibiscus sabdariffa L.) - Marini; Ayu Saputri; Nur Azizah (Jurnal Ilmiah Manuntung: Sains Farmasi Dan Kesehatan, 2024)
Cosmetic hair dye preparations generally use synthetic dyes which often cause allergic reactions, one of which is Para-phenylenediamine. Butterfly pea flowers (Clitoria ternatea L.) and rosella flowers (Hibiscus sabdariffa L.) contain anthocyanins which can be used as natural dyes. The aim of this research was to formulate a hair coloring cream preparation from a combination of butterfly pea flower extract and rosella flower extract using three different formulas. The extraction method to extract the dye from both flowers uses the maceration method and 70% ethanol solvent. The dye resulting from the maceration of telang flowers is deep purple and for rosella flowers it is heart red, the combination of the two produces several color variations. The results of the cream formulation of butterfly pea flower extract and rosella flower extract with a ratio of 15:5 (F1) produce a royal purple color, a ratio of 10:10 (F2) produces a vivid violet color and a ratio of 5:15 (F3) produces plum. The results of the evaluation of the physical preparations of the three formulas met the requirements for homogeneity, pH and spreadability. The results of the color stability test showed that soaking for 4 hours produced hair color, purple (F1), light purple (F2) and light magenta (F3) and washing did not last long up to 15 times. The results of the color stability test against exposure to sunlight show that the color produced in the hair does not change with 5 hours of exposure to sunlight. The irritation test produces an irritation index of F0=0.11, F1=0.22, F2=0.27 and F3=0.22 which states that the irritation is very mild.